SOCIAL DETERMINANTS AND PRE-EXISTING COMORBIDITIES ARE ASSOCIATED WITH SYMPTOMATIC COVID-19 IN A BRAZILIAN URBAN AREA (REMUNOM, 2026)
OBJECTIVE: To identify socioeconomic determinants and comorbidities associated with the presence of COVID-19 symptoms in Fortaleza, Ceará, Brazil.METHODS: A cross-sectional study based on a population-based household survey conducted between June and November 2020, including a representative sample of participants with confirmed SARS-CoV-2 infection.RESULTS: A total of 897 out of 1,541 individuals (58.2%) reported symptoms. Factors associated with symptomatic disease included female gender (Prevalence Ratio [PR] = 1.215; 95% CI: 1.098–1.344), age 20–39 years (PR = 1.312; 95% CI: 1.170–1.471) and 40–59 years (PR = 1.173; 95% CI: 1.052–1.308), and family income of up to one minimum wage (PR = 1.384; 95% CI: 1.051–1.821). Comorbidities such as hypertension, diabetes, asthma, chronic respiratory disease, and heart disease (PR ranging from 1.34 to 1.54) were significantly associated with symptomatic COVID-19. A higher proportion of symptomatic cases was observed among Indigenous individuals. In multivariable analysis, female gender (adjusted Odds Ratio [aOR] = 1.23; 95% CI: 1.07–1.41) and clinical conditions including hypertension (aOR = 1.52; 95% CI: 1.12–2.06), diabetes (aOR = 1.49; 95% CI: 1.00–2.21), asthma (aOR = 2.34; 95% CI: 1.21–4.50), chronic respiratory diseases (aOR = 3.23; 95% CI: 1.23–8.42), heart disease (aOR = 1.99; 95% CI: 1.07–3.70), and other comorbidities (aOR = 1.99; 95% CI: 1.07–3.70) were independently associated with symptomatic disease.CONCLUSION: The association between socioeconomic inequalities and preexisting diseases with symptomatic COVID-19 underscores the need for public policies aimed at reducing health inequities among populations at higher risk.